Pneumococcal colonisation and pneumonia severity in hospitalised Cambodian children following introduction of the 13-valent pneumococcal conjugate vaccine - Miliya, T; Soputhy, C; Leab, P; Tan, P; Sao, S; Heffelfinger, JD; Batmunkh, N; Ork, V; Hossain, MS; Turner, C; Day, NPJ; Turner, P (Elsevier, 2023)
Objectives This study sought to characterize pneumococcal colonization and clinical/radiological features in Cambodian children admitted to hospital with an illness compatible with pneumonia following national introduction of the 13-valent pneumococcal conjugate vaccine (PCV13).